Sleep and sleep-related breathing disorders in patients with spinal muscular atrophy: a changing perspective from novel treatments? - Abati, Elena; Mauri, Eleonora; Rimoldi, Martina; Madini, Barbara; Patria, Francesca; Comi, Giacomo Pietro; Corti, Stefania (Frontiers in Neurology, 2024)
Spinal Muscular Atrophy (SMA) is an inherited neuromuscular disorder characterized by progressive muscle weakness and atrophy, resulting from the degeneration of motor neurons in the spinal cord. A critical aspect of SMA is its impact on respiratory function. As the disease progresses, respiratory muscles, in particular intercostal muscles, become increasingly affected, leading to breathing difficulties and respiratory failure. Without intervention, many children with SMA type 1 die from respiratory failure before their second year of life. While assisted ventilation has improved survival, it often results in ventilator dependence. The development of new SMN-augmenting therapies has renewed optimism, but their long-term impact on respiratory function is uncertain, and non-invasive respiratory support remains an important part of SMA management. Despite the importance of respiratory support in SMA, knowledge regarding sleep disorders in this population is limited. This review aims to synthesize existing literature on sleep and sleep-related breathing disorders in patients with SMA, with a focus on SMA type 1. We summarize evidence of sleep-disordered breathing and respiratory failure in SMA, as well as outcomes and survival benefits associated with non-invasive or invasive ventilation with or without pharmacological therapies. We also discuss current knowledge regarding the effects of novel disease-modifying therapies for SMA on respiratory function and sleep. In conclusion, optimal care for children with SMA requires a multidisciplinary approach that includes neurology and respiratory specialists. This review highlights the importance of monitoring sleep and respiratory function in SMA, as well as the potential benefits and challenges associated with assisted ventilation combined with new therapies.